People of the spirit : exploring Luke's view of the church - Twelftree, Graham H.; Society for Promoting Christian Knowledge (Great Britain) (Grand Rapids, Mich. : Baker Academic ; London : Society for Promoting Christian Knowledge, 2009)
"Today's church suffers a crisis of confidence as a result of pluralism, globalism, and postmodernity. Seasoned New Testament scholar Graham Twelftree's historical exploration of Luke's view of the church contributes to the current conversation about what the church is and should do. Twelftree draws together various strands in Luke's Gospel and the Acts of the Apostles to show Luke's profound influence on the church and explain Luke's thought regarding the church's origin, nature, purpose, and mission. A final chapter proposes Lukan conclusions to such debated questions as the relationship between church and salvation; the relationship between the Spirit, water baptism, and glossolalia in Christian initiation; the question of infant baptism; the character of worship; the interplay of Scripture and experience; church structure and leadership; and the nature of Christian mission."--Publisher's description.
The issues -- Origins and purpose -- Jesus : the church modelled -- Salvation and the church -- The church as the people of God -- Luke's Pentecosts -- The spirit, tongues, and baptism -- Problems in the early church -- Worship -- Scripture and knowing God -- Experience and knowing God -- Early Catholic, Protestant, or charismatic? -- Mission : evangelism or social action or both? -- Listening to Luke.
Includes bibliographical references and indexes.
Keywords: Church -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Lukasevangelium; Ekklesiologie; Bible; Bible; Church -- Biblical teaching; Criticism, interpretation, etc